2012
DOI: 10.3892/ijmm.2012.1057
|View full text |Cite
|
Sign up to set email alerts
|

Guggulsterone inhibits melanogenesis in B16 murine melanoma cells by downregulating tyrosinase expression

Abstract: Abstract. In the present study, we investigated the effect of guggulsterone on melanogenesis in B16 melanoma cells and elucidated its possible mechanism of action. The effects of guggulsterone on melanogenesis were determined by assaying melanin synthesis and cellular tyrosinase activity in B16/ F10 mouse melanoma cells. Guggulsterone dose-dependently inhibited isobutylmethylxanthine (IBMX)-induced melanogenesis and cellular tyrosinase activity with no cytotoxicity. Decreased melanin biosynthesis was accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The synthesis of melanin in melanocytes can be induced by numerous factors, including α-MSH, cyclic adenosine monophosphate (cAMP)-elevating agents (such as isobutylmethylxanthine and forskolin) and UV light [23,24]. Finding agents to regulate melanin synthesis is important for the treatment of hyper- or hypo-pigmentation [25,26,27].…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of melanin in melanocytes can be induced by numerous factors, including α-MSH, cyclic adenosine monophosphate (cAMP)-elevating agents (such as isobutylmethylxanthine and forskolin) and UV light [23,24]. Finding agents to regulate melanin synthesis is important for the treatment of hyper- or hypo-pigmentation [25,26,27].…”
Section: Resultsmentioning
confidence: 99%
“…Second, we found that melanogenesis of B16F10 cells by the MA extract (20 µg/ml) was rapid and that the pellet color of cells was enhanced within 4 h after treatment. To compare the melanogenic effect of MA with other agents, we used the well-known melanogenic inducer forskolin at a concentration (20 µM) that is higher than the concentrations (5 or 10 µM) usually used in other groups (34,35). After incubation with the MA extract (20 µg/ml) for 8 h, the pellet color was darker than that incubated with forskolin (20 µM) for 48 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Microphthalmia-associated transcription factor (MITF), which is one of the most important nuclear activation transcription factors of tyrosinase, TRP-1 and TRP-2, plays key role in melanocyte development regulation and survival [37, 38]. Our results showed that apigenin-7-butylene glucoside had no effects on the MITF transcription and translation levels in B16-F10 cells as shown in Figures 5 and 6, though the MITF was reported to be the master regulator in the transcription of genes which were involved in melanin synthesis.…”
Section: Discussionmentioning
confidence: 99%